Chemical Potential of Benzene Fluid from Monte Carlo Simulation with Anisotropic United Atom Model - Mahfuzh Huda; Siti Mariyah Ulfa; Lukman Hakim (Chemistry Department, The University of Brawijaya, 2013)
The profile of chemical potential of benzene fluid has been investigated using Anisotropic United Atom (AUA) model. A Monte Carlo simulation in canonical ensemble was done to obtain the isotherm of benzene fluid, from which the excess part of chemical potential was calculated. A surge of potential energy is observed during the simulation at high temperature which is related to the gas-liquid phase transition. The isotherm profile indicates the tendency of benzene to condensate due to the strong attractive interaction. The results show that the chemical potential of benzene rapidly deviates from its ideal gas counterpart even at low density.